THE ROLE OF PUBLIC PARTICIPATION AND GOVERNMENT POLICY ON REDUCING THE SPREAD OF THE COVID 19 VIRUS IN MADURA INDONESIA - Agus Sugiyardi; Nurul Hidayati (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2021)
The purpose of this study was to determine the effect of Public Participation and Government Policies on Reducing the Spread of the Covid 19 Virus. This research is classified as explanatory research with a quantitative approach. The sample used was 100 respondents. The sample in this study is the community in four districts in Madura, Indonesia. This research used purposive sampling technique. The type of data used is primary data, namely collecting data using questionnaires. Analysis of the data used is Multiple Linear Regression Analysis. The result of this research shows that Public Participation has a significant effect on Government Policy, Government Policy has a significant effect on Reducing the Spread of the Covid 19 Virus, and Public Participation has a significant effect on Reducing the Spread of the Covid 19 Virus.